ABI4 represses the expression of type‐A ARRs to inhibit seed germination in Arabidopsis. (25th January 2017) - Huang, Xiaozhen; Zhang, Xiaoyan; Gong, Zhizhong; Yang, Shuhua; Shi, Yiting
Summary: The plant hormone abscisic acid (ABA) plays a crucial role in regulating seed germination and post‐germination growth. ABSCISIC ACID INSENSITIVE4 (ABI4), an APETALA2 (AP2)‐type transcription factor, is required for the ABA‐mediated inhibition of seed germination. Cytokinins promote seed germination and seedling growth by antagonizing ABA signaling. However, the interaction between ABA and cytokinin signaling during seed germination remains unclear. Here, we report that ABA signaling downregulates Arabidopsis response regulators ( ARRs ), a class of cytokinin‐inducible genes, during seed germination and cotyledon greening. We found that the application of exogenous ABA repressed the expression of type‐A ARRs in Arabidopsis seeds and seedlings. Among the type‐A ARR family members, the expression of ARR6, ARR7 and ARR15 was upregulated in ABA‐deficient mutants, indicating that the transcriptional inhibition of type‐A ARRs requires the ABA signaling pathway. Single and multiple mutations of these ARRs resulted in increased ABA sensitivity during germination and cotyledon greening; overexpression of ARR7 or ARR15 led to an ABA‐insensitive phenotype. These observations suggest that type‐A ARRs inhibit the ABA response during seed germination and cotyledon greening. Further analysis showed that ABI4 negatively regulated the transcription of ARR6, ARR7 and ARR15 by directly binding to their promoters. Genetic analysis showed that loss‐of‐function mutations of ARR7 and ARR15 partially rescued the ABA insensitivity of abi4‐1 . Thus, this study revealed that ABI4 plays a key role in ABA and cytokinin signaling by inhibiting the transcription of type‐A ARRs to inhibit seed germination and cotyledon greening. Significance Statement: The plant hormone abscisic acid (ABA) suppresses seed germination, while cytokinin promotes seed germination and seedling growth. The detailed molecular mechanisms underlying ABA and cytokinin antagonism during seed germination remain elusive. Here we report that the transcription factor ABI4 negatively regulates the expression of Arabidopsis response regulators ( ARRs ), a class of cytokinin‐inducible genes. Thus ABI4 is a key node that integrates ABA and cytokinin signalling to modulate seed germination and cotyledon greening.